THE FORMALION OF LANGUAGE POLITICS IN THE KYRGYZ RESPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the formation of language policy in the Kyrgyz Republic, the external and internal conditions that determined it. Some measures taken to develop language policy are considered
Keywords: language police, national language, world language, globalization , linguistic situation, language law, language planning